The necessity of nature : God, science and money in 17th century English law of nature - García-Salmones Rovira, Mónica (Cambridge studies in international and comparative law, 2023)
"This is a study of the philosophy and theology of the Scientific Revolution and its impact on European natural law and political liberalism. It analyses transformations of the concept of sacred nature and the human light of reason leading to the Anthropocene, and fluctuations between human necessities and scientific money"--
Keywords: 1600-luku; historia; lait; luonnonoikeus; luonto; tieteellinen maailmankuva; tiede; teologia; talous; oikeusjärjestys; Natural law : History : 17th century; Natural law : England : History : 17th century; Englanti